[RETRACTED] The Paradox of Regional Development in Mandalika: An Augmented Qualitative Phenomenology Study on Child Labor Household - Raja Sahing, Intan Tiani; Prestianawati, Silvi Asna (Journal of Development Economic and Social Studies, 2025)
[RETRACTED] Reducing regional development disparities is one of the key focuses of the Sustainable Development Goals (SDGs). The establishment of Special Economic Zones (SEZs) is one of the Indonesian government's efforts to enhance the equitable welfare of its society. One such SEZ is Mandalika in Central Lombok, which is currently being developed into a major investment magnet and tourism destination in Indonesia. However, a paradoxical phenomenon has emerged during this development process: the rise of child labor in Mandalika. Therefore, this study aims to uncover and analyze the phenomenon of child labor in Mandalika as a Special Economic Zone in Central Lombok, using the household perspective of child laborers and employing the augmented qualitative phenomenology method. The results indicate that poverty and the low educational levels of households with child laborers are the main factors driving children into the workforce. Furthermore, despite the low educational levels of the parents, they are determined to support their children’s education. In terms of health, households of child laborers in Mandalika exhibit low health literacy, as evidenced by all study participants lacking BPJS (Indonesia's health insurance) and being unable to provide nutritious food for their children. This study contributes as a stepping stone for both regional and national governments to focus on non-physical development in Mandalika, particularly improving education and human resources. Building physical infrastructure in Mandalika without accompanying human resource development would hinder the optimal impact of such development on the community. This study is also valuable for policymakers in planning comprehensive and participatory child labor alleviation strategies. The output of this research is expected to generate a strategic policy design for the local government of Central Lombok.